Meteological Observations during the JARE South Pole Traverse1968-69 - Nishibe, Nobukazu; Seino, Zenbei (1971)
P(論文) Throughout the period of traverse, September 28,1968 to February 13,1969,surface meteorological observations were carried out at 06,12,and 18 GMT, except the days spent at the Plateau Station and the South Pole Station. The technical details of observation were all in accordance with WMO's regulations. departmental bulletin paper